Fatigue life prediction of pile-supported sea-crossing bridges subject to random ice forces - Wu, Tianyu; Qiu, Wenliang (Journal of constructional steel research, 2022)
As a natural disaster in cold sea regions, ice forces can cause strong vibration of offshore structures, and even threaten the safety of structures. The elevated steel pile caps are the most commonly used substructure foundation type of sea-crossing bridges and the large-scale caps are generally used to resist ice forces. The fatigue damage of sea-crossing bridges with steel piles under ice forces is directly related to the fluctuating stresses. Therefore, this paper carried out the fatigue damage analysis and fatigue life prediction of sea-crossing bridges subjected to random ice forces in Bohai Sea. In order to considering long-range condition of sea ice, the statistical characters of sea ice properties such as, ice velocity, ice thickness and ice strength are carried out. The ice forces processes are simulated utilizing the random ice force spectrum model for vertical and conical structures. Fatigue damage of sea-crossing bridges with vertical and conical caps is analyzed using the rainflow cycle counting technique and Palmgren-Miner's rule. The fatigue life is estimated based on the cumulative fatigue damage and the real period of drift ice in Bohai Sea. Results show that the fatigue damage increases obviously as a result of increases in the stress caused by increased sea ice parameters. The sea-crossing bridges with conical caps can prolong the fatigue life by more than 45% in comparison with sea-crossing bridges with vertical caps. The cone ice-resistant cap has a good effect on mitigating fatigue damage of sea-crossing bridges in drift ice covered water regions. The graphical abstract is preparation of the simulation process for fatigue life prediction of sea-crossing bridges under random ice forces. As a natural disaster in cold sea regions, ice forces can cause strong vibration of offshore structures, and even threaten the safety of structures. The elevated steel pile caps are the most commonly used substructure foundation type of sea-crossing bridges and the large-scale caps are generally used to resist ice forces. The fatigue damage of sea-crossing bridges with steel piles under ice forces is directly related to the fluctuating stresses. Therefore, this paper carried out the fatigue damage analysis and fatigue life prediction of offshore bridges subjected to random ice forces. In order to considering long-range condition of sea ice in Bohai Sea, the statistical characters of sea ice properties such as, ice velocity, ice thickness and ice strength are carried out. The ice forces processes are simulated utilizing the random ice force spectrum model for vertical and conical structures in Bohai Sea. Fatigue damage of offshore bridges with vertical and conical caps in Bohai Sea is analyzed using the rainflow cycle counting technique and Palmgren-Miner's rule. The fatigue life is estimated based on the cumulative fatigue damage and the real period of drift ice in Bohai Sea. The method proposed in this paper can be used to predict the fatigue life of sea-crossing bridges in cold regions under ice induced vibration. [Display omitted] •A simulation method of random ice force process based on random ice force spectrum model was proposed.•Sub-structure interactions include water–structure interaction, and soil–structure interaction.•The random ice forces were treated as external loads input to the bridge-soil interaction model.•A fatigue damage assessment method for sea-crossing piles-supported bridges under ice forces was proposed.•The performance of bridges with vertical and conical caps in mitigating fatigue damage was evaluated.